Iterative methodology to improve the resources utilization rate of a production system - Shih, Chin (2009)
The management of production resources is an important activity to acquire competitive advantage, which its goal is to integrate the equipments aiming at attending the demand with a lower final product price. This paper presents a typical issue in production resources management which when extra capacity of bottleneck equipment is added, it generates over sizing and therefore idle. In addict to this, this decision may transfer the bottleneck to other equipments. A model in discrete simulation in Arena® 5.0 is constructed and executed to monitor the bottleneck formation, based on the information of the utilization rate. Next, it is presented in this paper an iterative methodology to improve the utilization rates of all equipments, obtained from the mathematical modeling of balancing elements which pass through the production system. This methodology can be easily implemented in programming software Pascal 7.0.